If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = 4 + 3y Solving -2 = 4 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -2 + -3y = 4 + 3y + -3y Combine like terms: 3y + -3y = 0 -2 + -3y = 4 + 0 -2 + -3y = 4 Add '2' to each side of the equation. -2 + 2 + -3y = 4 + 2 Combine like terms: -2 + 2 = 0 0 + -3y = 4 + 2 -3y = 4 + 2 Combine like terms: 4 + 2 = 6 -3y = 6 Divide each side by '-3'. y = -2 Simplifying y = -2
| 10z-5-2z=11+4z | | 15x^2+11x-12=-12 | | 14+n=18 | | 5x+22=3x+14 | | 10=4w+2 | | 4x+2y-6=10 | | 2x^2-180=0 | | 6x-1=15x+100 | | 18=-3+w | | Ix+1l=5 | | 2u+5=-5 | | logx(x+1)=0 | | loge(x+1)+loge(x)=0 | | x-38=6 | | y=x^2-11x+90 | | 3*x+y=1250 | | y=x^2+6x-36 | | (x-4)(x+3)=3x-7 | | f(x)=x^2+14x+55 | | log(x^2-1)=log(x+5) | | cosx+cotx=3 | | x^2-9x+20=2 | | -5-2b-8=4b-1-2b+7-8b | | (55*32)X=313*X | | -10=g-14 | | 25=3(5x-1)-x | | H-20=-8 | | F(-4)=5-4x | | F+19=4 | | y+5=10y-8 | | f(x)=4x^2+8x-3 | | 9x=-25+2x |